PENGEMBANGAN MEDIA KOMIK DIGITAL BERBANTUAN APLIKASI CARTOON STORY MAKER PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Priadi, Aam; Aunurrahman, Aunurrahman; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to develop a Digital Comic with the Cartoon Story Maker Application on thematic learning in elementary schools and to describe the acquisition of learning outcomes using the digital comic with the Cartoon Story Maker Application on thematic learning in elementary schools. This study uses the research model of Borg, WR, Gall, MD, & Gall, JP then adopted by Sugiyono into 7 steps of the development stage namely potential and problems, data collection, product design, design validation, product revision, product trials, and product revisions . Before carrying out product trials, the comic media expert validation and thematic learning expert validation are carried out. The study subjects contains 3 students for individual trials, 9 students for small group trials and 15 people for large group trials. The results of the study describe that (1) the design of a digital comic product with seven steps obtains very good criteria for thematic learning in primary schools, with details of motivational aspects with an average of 4.52 or 90.67%, aspects of program outcomes with an average of 4 , 55 or 90.93% and aspects of student effectiveness get an average of 5.56 or 91.11%, so it can be said that the design of digital comics aided by the application of Cartoon Story Maker is feasible to be used in learning in elementary schools. (2) Acquisition of student learning outcomes by using digital comics aided by the application of Cartoon Story Maker on thematic learning to get a significant result that is 2.142 with an effect size of 0.77 with a moderate category so that the use of digital comics developed based on 7 steps of research development can improve learning outcomes for learners in elementary schools. Keywords: Research and Development, Digital Comic Media, Thematic Learning